1‐kHz hybrid femtosecond/picosecond coherent anti‐Stokes Raman scattering thermometry of turbulent combustion in a representative aeronautical test rig. (6th April 2021) - Scherman, Michael; Barros, Joanna; Santagata, Rosa; Lin, Elodie; Nicolas, Philippe; Faleni, Jean Pierre; Vincent‐Randonnier, Axel; Cherubini, Pascal; Guichard, Florestan; Mohamed, Ajmal; Gaffie, Daniel; Attal‐Tretout, Brigitte; et al.
Abstract: The study of complex reactive flows met in aeronautical engines is an experimental challenge that requires the development of noninvasive and precise measurement techniques. Coherent anti‐Stokes Raman scattering (CARS) is a standard spectroscopic technique used for temperature measurements, which provides unmatched reliability and accuracy at high repetition rate thanks to its recent adaptation to femtosecond temporal regime. This paper reports the first demonstration of hybrid fs/ps‐CARS thermometry in a representative aeronautical combustor (ONERA MICADO test bench, Reynolds number ≈10 5 ). Single‐shot N2 CARS spectra have been recorded at 1 kHz, allowing temperature follow up, statistical and frequency (0.1–500 Hz) analysis of CH4 /air flame at 0.34‐MPa total pressure. The achieved results demonstrate the ability of the technique to be applied in representative engines conditions and its maturity for semi‐industrial applications. Abstract : This paper reports the first demonstration of hybrid fs/ps‐CARS thermometry in a representative aeronautical combustor (ONERA MICADO test bench, Reynolds number ≈10 5 ). Single‐shot N2 CARS spectra have been recorded at 1 kHz, allowing temperature follow up, statistical and frequency (0.1–500 Hz) analysis of CH4 /air flame at 0.34‐MPa total pressure. The achieved results demonstrate the ability of the technique to be applied in representative engines conditions and its maturity for semi‐industrial applications.